Desenvolvimento e aplicações de células e eletrodos impressos em 3D para a triagem e determinação de fármacos de interesse forense - Ferreira, Priscila Alves (2022)
The spread of counterfeit, smuggled and low-quality medicines has raised concern among health authorities in several countries due to the numerous risks they pose to the population. Electroanalytical techniques are a quick and low-cost alternative to performing the screening of illegal drugs at the place of seizure. In Chapter II, two methodologies for rapid determination and screening of tadalafil (TAD) are presented, using a 3D printed Batch Injection Analysis (BIA) with amperometry detection and multiple pulse amperometry, respectively. The results obtained were compared with the determination of TAD by spectrophotometry and the statistical data confirm that there was no difference between the values obtained by both techniques. In the second procedure, the screening of adulterated TAD samples was performed and, through the normalization (ratio) of peak currents, it was possible to distinguish between authentic and adulterated samples. In Chapter III, a 3D printed electrochemical cell compatible with several planar electrodes was proposed, consisting of a reservoir, rod and cap with pseudo-reference and auxiliary electrodes made with conductive filament extruded by a 3D pen. 3D-MSEC was applied in the screening of active ingredients in drugs with a history of counterfeiting/tampering, such as sildenafil citrate (SC), losartan, tadalafil and 17 α-ethinylestradiol. In this screening procedure, direct abrasion of the powder of each drug was performed on the graphite sheet electrode (GS), followed by mounting on the 3D-MSEC and recording the voltammetric profile in the presence of only 500 L of electrolyte. This set is promising for the rapid and practical screening of illicit drugs to identify the absence or presence of the active ingredient, as well as electroactive impurities. In Chapter IV, 3D-MSEC/GS was applied in the screening and determination of SC in Brazilian and Paraguayan drugs, and the results were compared with HPLC. This device was also applied in the screening of SC drugs seized by the Civil Police of Belo Horizonte-MG. The results showed the presence of SC alone in some samples and combined with other substances in others. KEYWORDS: 3D printing; 3D additive manufacturing; Fusion and Deposition Modeling (FDM); 3D pen; Screening of counterfeit drugs.